DTC Method for Vector Control of 3-Phase Induction Motor under Open-Phase Fault - M. Jannati; N. R. N. Idris; M. J. A. Aziz (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Three-phase Induction Motor (IM) drives are widely used in industrial equipments. One of the essential problems of 3-phase IM drives is their high speed and torque pulsation in the fault conditions. This paper shows Direct Torque Control (DTC) strategy for vector control of a 3-phase IM under open-circuit fault. The objective is to implement a solution for vector control of 3-phase IM drives which can be also used under open-phase fault. MATLAB simulations were carried out and performance analysis is presented. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6910